Enzymatic and immunological properties of Bungarus flaviceps (red-headed krait) venom - Tan, N.H.; Fung, Shin Yee; Ponnudurai, G. (BMC, 2010)
Bungarus flaviceps (red-headed krait) venom presents an intravenous LD50 of 0.32 Î¼g/g and exhibits enzymatic activities similar to other Bungarus toxins. ELISA cross-reactions between anti-Bungarus flaviceps and a variety of elapid and viperid venoms were observed in the current study. Double-sandwich ELISA was highly specific, since anti-B. flaviceps serum did not cross-react with any tested venom, indicating that this assay can be used for species diagnosis in B. flaviceps bites. In the indirect ELISA, anti-B. flaviceps serum cross-reacted moderately with three different Bungarus venoms (9-18) and Notechis scutatus venom, but minimally with other elapid and viperid toxins. The results indicated that B. flaviceps venom shares common epitopes with other Bungarus species as well as with N. scutatus. The lethality of the B. flaviceps venom was neutralized effectively by antiserum prepared against B. candidus and B. flaviceps toxins and a commercial bivalent elapid antivenom prepared against B. multicinctus and Naja naja atra venoms, but was not neutralized by commercial antivenoms prepared against Thai cobra, king cobra and banded krait. These data also suggested that the major lethal toxins of B. flaviceps venom are similar to those found in B. multicinctus and B. candidus venoms.